STRATEGI PENGUATAN KELEMBAGAAN KELOMPOK TANI DALAM USAHATANI AGROFORESTRY: KASUS KELOMPOK TANI KECAMATAN SODONGHILIR, TASIKMALAYA - Idin Saepudin Ruhimat (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2021)
Institutional strengthening can be used as a solution to improve performance of farmer groups, therefore a strategy for institutional strengthening of farmer groups is needed in agroforestry farming development. The study aimed to analyze strategic factors, examine various alternative strategies, and formulate strategic priority recommendations as an effortto strengthen farmer groups in agroforestry farming development. The study was conducted at Sodonghilir District - Tasikmalaya Regency, West Java Province from April to August 2018. Data were analyzed using Strength, Weakness, Opportunity, Threat (SWOT) and Quantitative Strategic Planning Matrix (QSPM) analysis. The results showed that the institutional weakness of farmer groups affected the success of agroforestry farming development in Sodonghilir District. Based on this research, it can be concluded that internal and external factors are two strategic factors that must be used as the basis for the formulation of two priority strategies from six alternative strategies for institutional strengthening of farmer group in agroforestry farming. The two priority strategies are increasing human resources capacity as well as increasing farmer groups’ role in agroforestry farmingdevelopment. Therefore, it is recommended that farmer groups, national and regional governments to prioritize these two of institutional strengthening strategies in agroforestry farmingdevelopment